2015
DOI: 10.1038/srep17127
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the small GTPase SAR1A: a key event underlying alcohol-induced Golgi fragmentation in hepatocytes

Abstract: The hepatic asialoglycoprotein receptor (ASGP-R) is posttranslationally modified in the Golgi en route to the plasma membrane, where it mediates clearance of desialylated serum glycoproteins. It is known that content of plasma membrane-associated ASGP-R is decreased after ethanol exposure, although the mechanisms remain elusive. Previously, we found that formation of compact Golgi requires dimerization of the largest Golgi matrix protein giantin. We hypothesize that ethanol-impaired giantin function may be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 73 publications
14
57
0
Order By: Relevance
“…We hypothesized that these additional targets of miR‐18a and miR‐25 may also play key roles, together with SOCS5, in promoting or maintaining HCC in a combinatorial manner. Interestingly, knockdown of SAR1A in normal hepatocytes was shown to mimic the effect of chronic alcohol consumption on liver damage . The tumor suppressor TSC1 is a key repressor of the mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that these additional targets of miR‐18a and miR‐25 may also play key roles, together with SOCS5, in promoting or maintaining HCC in a combinatorial manner. Interestingly, knockdown of SAR1A in normal hepatocytes was shown to mimic the effect of chronic alcohol consumption on liver damage . The tumor suppressor TSC1 is a key repressor of the mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, knockdown of SAR1A in normal hepatocytes was shown to mimic the effect of chronic alcohol consumption on liver damage. 41 The tumor suppressor TSC1 is a key repressor of the mTOR signaling pathway. Our results demonstrated that SOCS5 regulates the expression of TSC1 as well as downstream mTOR signaling (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other small GTPases, including RhoA, Rac1, and Sar1a, have been found to be impaired by exposure to EtOH 46, 47, 48, 49. It is possible that EtOH directly acts on these GTPases (e.g., interfering with posttranslational lipid modifications) or perhaps functions indirectly on known guanine nucleotide exchange factors, preventing appropriate GTP cycling and an inability of these enzymes to bind nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…(26) In man and animal, chronic alcohol feeding with nutritionally adequate diets induced ultrastructural abnormalities of hepatocytes. (27) There is also an adaptive Golgi stress response (GSR) that involves Golgi resident protein 60 (GCP60), heat shock protein 47 (HSP47), and transcription factor for immunoglobulin heavy-chain enhancer 3 (TFE3) to cope with disrupted homeostasis of the Golgi. (21,22) However, persistent stress on the Golgi disturbs metabolism in the liver, and dysfunction of the Golgi apparatus is associated with various stress-induced liver injuries.…”
Section: Introductionmentioning
confidence: 99%